Pharmacist-led Smoking-Cessation Services in the United States - A Multijurisdictional Legal Analysis - Landon S. Bordner; Joseph Lavino (University of Minnesota Libraries Publishing, 2022)
A challenge presents itself when pharmacy students and pharmacists have the knowledge, skills, and abilities to provide optimal patient care, which can prevent the healthcare industry from incurring expenditures reaching billions of dollars annually from chronic and acute disease state management, yet due to the lack of statutory or regulatory authority to independently prescribe and dispense smoking cessation products they are unable to tap into this potential.  Prescriptive authority of pharmacists is not a novel concept; however, State Legislatures and Boards of Pharmacy have been slow to  expand upon the pharmacist's scope of practice to include this authority. As a consequence, this inaction hinders the opportunity of almost 21.5 million patients, who attempt to quit smoking annually, the ability to access a U.S. Food and Drug Administration approved, evidence-based medication-assisted or nicotine replacement therapy prescribed by a pharmacist.2 Current legislative efforts, laws, and regulations regarding a pharmacist's prescriptive authority for tobacco cessation therapy vary greatly amongst the states and do not include reference to e-cigarettes or electronic nicotine delivery systems (e.g., e-cigs, vape pens, vapes, mods, etc.). Additionally, pharmacists are often required to practice under a statewide protocol or enter into a collaborative practice agreement ("CPA") with a designated physician, which are often complex and create significant barriers for the pharmacist to practice at the top of their license and for the benefit of the patient. This legal and regulatory study reveals the following: 1) Those States that have addressed or attempted to address the pharmacist's prescriptive authority for tobacco cessation therapy, 2) the authority to independently prescribe vs. practice under a statewide protocol, 3) the products able to be prescriber or dispensed under the pharmacist's prescriptive authority or statewide protocol, and 4) the guidelines and/or protocols referenced within their respective State laws and regulations. States and their residents would benefit greatly from amending their laws and regulations to expand upon the pharmacist's prescriptive authority, granting them the ability to help their communities by performing services they are highly trained to perform.